Pegando vida nas mãos: um olhar etnográfico sobre saberes e práticas das parteiras tradicionais nos circuitos do Amapá em mudanças - Silva, Alzira Nogueira da (2005)
Hand Delivering: An Ethnographic Outlook on Changing Knowledge and Practices of Traditional Midwives (“Pegando Vida nas Mãos”: um olhar etnográfico sobre saberes e práticas das parteiras tradicionais nos circuitos do Amapá em mudanças) is the upshot of an investigative trail followed in the pursuit of unveiling the world of knowledge and practices of traditional midwives from Mazagao/Amapa. The investigation is set within the realm of the Social Sciences shaping up an ethnographic study that encompasses a frontier area between Sociology and Anthropology. Indeed, I tried to develop a sociological approach about a web of relations that define the profession of traditional midwives resorting to a methodological tool from ethnography. To set out on this ethnographic adventure I took as a basic assumption the thesis that the job of helping delivery implies an interaction process of “midwife and parturient” that includes partnership, female solidarity, power struggle, respect and leadership that add to this relation a complex web of feelings for the sharing of life and culture. My analysis posts knowledge and practices, as seen by the performance of traditional midwives from Mazagao, within peculiar sociability forms in traditional communities in the Amazon basin in order to grasp the meaning of multiple converging elements produced by knowledge and practices of women from the region. In this investigation I tried to unveil the web of meanings that involves the traditional practice of midwives from Mazagao within conflicting dynamics of meanings found in their knowledge/practices considering that within a given political context those practices and the web that they form go through changes and adjustments according to intervention programs of the State that sometimes have punctual and temporary aspects that impact the informal webs.